TREND ANALYSIS OF RAINFALL, LANDUSE, AND RUNOFF IN CITARUM-MAJALAYA BASIN - Rizaldi, Akbar
Floods and droughts are important issues related to water resources that have been studied recently. The cause of the bias is caused by large changes in land cover or even the climate of a region undergoing a change. Climate change itself is a global issue that concerns the world in the last few decades. Some researchers, especially in developed countries have conducted data analysis to detect climate behavior in the study area based on historical data records owned. Neither is the change of land cover that is a human need which inevitably has to be done to improve the living standard of man himself. Runoff discharge, land cover, and rain are related to each other. By knowing several variable we can know the condition of other variables and the three variables that have been mentioned can show the condition of catchment area. This study aims to determine trend of rainfall data, land cover and runoff discharge in the Citarum-Majalaya Watershed Area. From the results of the analysis it was found that the runoff increased 53 m3/s based on the maximum recorded runoff discharge in period (1999-2016). Then, rainfall is also increase during the last 30 years, while land cover variables tend to be constant. Then we find the equation of the relationship between the discharge and the rain where the discharge (Q) = 0.2319 (CH) +4,9267. Then it was found that the phenomenon that shows the value of rain that occurs unevenly based on rain and debit data recorded on each record post. And also when the flow was analyzed using corrected satellite data, the same phenomenon is occurr. Although satellite data is alvailable than the ground station. The results of the analysis process using GSMap satellite data show rain data has a better correlation than existing rainfall record data. With a good correlation value indicates the occurrence of rain that is not detected the post of the existing record is known the amount of rain that occurs. In the analysis of the event base model of rainfall data that more represents the discharge is the rainfall data from GSMap satellite. Based on the results of rainfall-runoff modeling conducted using data from 1999-2016 and the scenario of land cover and without land cover shows with the scenario of land cover changes that occur actually decrease the trend / tendency of runoff discharge value resulting in rainfall-runoff daily model. However, after a simulation of extreme events, land cover changes actually detected increased by about 9%. This does not indicate that extreme discharge models have more accuracy than daily discharge models. The resulting CN value represents only the amount runoff occurred after rain event, not represents the condition of land cover of study area. Based on the test using the Mann-Kendall Test on rainfall rainfall data, debit, satellite rain post and CN values generated by the model, it was found that there was a trend or positive trend in rainfall rainfall data, maximum annual debit data, and maximum regional rainfall according to the lapse of each data recording. While on the CN data, after testing the trend found no detectability of the CN value in the Citarum-Majalaya watershed region.